Suburbanization and migration in Polish metropolitan areas during political transition - Gałka, Jadwiga; Warych-Juras, Anna (Acta geographica Slovenica, 2018)
This article presents the development of suburbanization processes that occurred in Polish metropolitan areas during the political transition from communism. We analyze data on population and migration for municipalities in seven metropolitan areas from 1995 to 2012. Our results show that the suburban development phase was strongly associated with cities’ size and level of economic development. The article concludes that the outflow of the urban population to the suburbs started earliest in centers that had successfully undergone the transition period.